2015
DOI: 10.1186/s12930-015-0021-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an early_exposure program on medical students’ interest in and knowledge of rural medical practices: a questionnaire survey

Abstract: BackgroundMany medical students in Japan were brought up in urban areas, thus rural medical practice is often unfamiliar to them. The University of Tsukuba created a one-day early_exposure program to provide freshman students with experience in rural practices. This study was designed to clarify how this one-day early_exposure program affected medical students’ attitudes toward and knowledge of rural practices.FindingsFirst-year medical students (n = 103) were assigned to one of seven rural clinics in which th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…It seemed likely that most of the medical students who chose rural medical institutions for clinical clerkships were interested in rural medical work. Consistent with previous studies conducted in Japan [ 18 ], Australia [ 19 ], America [ 20 22 ], and New Zealand [ 23 ], this study demonstrated a significant association between medical students’ experiences with rural medical clerkships and their intentions to choose rural medical work after graduation. The results indicated that medical students who had experience with a rural clinical clerkship were 1.25 times more likely to have intentions to work in rural medical institutions after graduation than those without relevant experience.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It seemed likely that most of the medical students who chose rural medical institutions for clinical clerkships were interested in rural medical work. Consistent with previous studies conducted in Japan [ 18 ], Australia [ 19 ], America [ 20 22 ], and New Zealand [ 23 ], this study demonstrated a significant association between medical students’ experiences with rural medical clerkships and their intentions to choose rural medical work after graduation. The results indicated that medical students who had experience with a rural clinical clerkship were 1.25 times more likely to have intentions to work in rural medical institutions after graduation than those without relevant experience.…”
Section: Discussionsupporting
confidence: 90%
“…A large number of medical schools in many countries had implemented the relevant strategy of offering medical students opportunities to practice in rural areas as part of their educational experience. In Japan, the University of Tsukuba created a one-day early-exposure program to provide fresh students with experience in rural practices, which demonstrated a positive impact on medical students’ interest in rural medical practice, with an increase from 39.0% (pre-program) to 61.0% (post-program) [ 18 ]. In Australia, medical students from three universities (the Universities of Sydney, Wollongong and Adelaide) were involved in a longitudinally integrated placement program that enabled medical students to live and work in a rural and remote setting and surrounding regions for 6–12 months for clinical learning, and this powerfully influenced their intentions to practice rurally [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, improving the RTMSs’ satisfaction with the educational scheme in the medical university seems to be very conducive to the students’ intentions of remaining in rural areas after the contract expired. Related studies have found that improving the curricular design (i.e., matching curricula with rural health needs and implementing early exposure and experience to rural medical work) could increase medical students’ interest in rural medical practice [ 24 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is also essential to ensure that trainees have a high quality of life while living in the community, with improved living environments and support programs. To achieve this, it is necessary to share best practices among neighboring hospitals, continuously enhance training programs, and to listen to the trainees' opinions, all under close collaboration with each community's major hospitals and university hospitals' postgraduate clinical training centers [14][15][16].…”
Section: Improvement Of Regional Policy For Community Medicinementioning
confidence: 99%